Typologies and patterns of information architecture: Present in the user interfaces of social networks of Meta (Instagram and Facebook) - Rodríguez-Perujo, Germán; Rodrigo-Martín, Isabel; Muñoz-Sastre, Daniel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Information Architecture (IA) organises digital content, from web interfaces to ATM screens and car dashboards. In addition to structure, it encompasses the labelling and organisation of information in each interface. It is presented through mind maps and is essential in both academic and professional environments. In complex products such as social networks, several IA patterns are employed simultaneously. This research introduces IA to Applied Communication Sciences, highlighting its importance for improving User Experience in social networks. This study identifies standard patterns and new types of mental maps for digital creation.